2017
DOI: 10.1590/1413-81232017229.16492017
|View full text |Cite
|
Sign up to set email alerts
|

Lesões provocadas por armas de fogo atendidas em serviços de urgência e emergência brasileiros

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 15 publications
2
10
0
11
Order By: Relevance
“…In 2014 A study in Brazil aimed to analyze the care of people injured by firearms in Brazilian emergency services, in 24 capitals indicated that 1.5% for self-caused injuries, 15.9% for aggression and 65.1% for legal intervention were caused by firearm. There was predominance of assistance to male patients, young adults (20 to 39 years old), brown skin color and low schooling (13).…”
Section: Discussionmentioning
confidence: 98%
“…In 2014 A study in Brazil aimed to analyze the care of people injured by firearms in Brazilian emergency services, in 24 capitals indicated that 1.5% for self-caused injuries, 15.9% for aggression and 65.1% for legal intervention were caused by firearm. There was predominance of assistance to male patients, young adults (20 to 39 years old), brown skin color and low schooling (13).…”
Section: Discussionmentioning
confidence: 98%
“…A via pública (85%) é o local de ocorrência com maior incidência de crimes (Duarte, 2019;Rodrigues et al, 2018;Ribeiro, Souza & Sousa, 2017;Souto et al, 2017;Fernandes, 2016). A ação criminal geralmente é praticada por dois infratores (47,05%) estando estes a pé (39,58%) ou utilizando o carro (31,25%) como meio de locomoção no momento do fato.…”
Section: Discussionunclassified
“…Una revisión de literatura advirtió que la prevalencia promedio de LP en pacientes con trauma de la médula espinal en los países en desarrollo fue de 35,2%, variando entre 26,7 y 46,2% (18) . El gasto del sistema público de salud con individuos que son víctimas de violencia ha aumentado gradualmente, lo que también afecta a las familias, que no pueden pagar los costos y la atención (19) .…”
Section: Discussionunclassified